IMPACT OF QUR’ANIC MORAL EXCELLENCE ON THE LIVES OF MUSLIM SOCIETY: AN EXPOSITION - Sule, Muhammad Maga; Mainiyo, Attahir Shehu (Fakultas Agama Islam Universitas Islam As Syafi'iyah, 2024)
The Glorious Qur’an, as the central religious text of Islam addresses various aspects of human life and provides guidance for personal and societal development. It also outlines the moral excellence for individuals and communities, focusing on spiritual, moral and social dimensions. The Glorious Qur’an recognizes the challenges faced by humanity and encourages efforts towards global human development. It however harps on the cultivation of moral virtues and ethical behavior thereby promoting justice, honesty, compassion, humility, patience and generosity. Principles of social justice and equality and the calls for eradication of discrimination based on race, gender as well as social status have aptly been captured in a plethora of Qur’anic verses. It is thus in line with this backdrop that this article intends to assess the impact of Qur’anic moral excellence on the lives of Muslim society towards human moral development. However, to achieve the objectives of the research, the article attempts to answer some basic questions. How did the Qur’an emphasize the need for social cohesion and working together to address societal challenges? What efforts are necessary for enhancing human moral development? What are the contributing factors toward promoting justice, peace and well-being of human society? What are the principles the Qur’an provides for effective navigation towards a better future for all? The article adopts analytical methodology.